Endogenous glutathione biosynthesis and GsiB-dependent glutathione uptake contribute to oxidative stress resistance in Vibrio alginolyticus - Liting Xu; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Qingxi Han; Weiwei Zhang (Journal of Invertebrate Pathology, 2026)

Enhancement of heavy metal electrokinetic removal and remediation in copper-zinc mine tailings by the anaerobic fermentation liquid byproduct addition: The synergistic effect of organic bio-acids - Jianru Liu; Xin Zhao; Junyu Chen; Liting Zhai; Lulu Qian; Enfei Qu; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Mpeg1 exerts direct bactericidal activity and mediates innate antibacterial function of B cells in Nile tilapia - Weiheng Shi; Yiwen Chai; Jugan Han; Yonglin Cai; Wuxian Fu; Yongya Luo; Yuhua Lin; Jianmin Ye; Liting Wu (Aquaculture, 2026)

Integrated hydrochemical assessment and health risk evaluation of coastal groundwater under seawater intrusion and anthropogenic influence in Weihai, North China - Linxian Huang; Kai Hu; Zhong Han; Xiaonong Hu; Liting Xing; Hui Liu; Hao Liang; Henghua Zhu (Environment, Development and Sustainability, 2026)

Diagnosing socioeconomic dominance in rainfall-runoff relationship changes across global basins - Xiaojing Zhang; Pan Liu; Lu Zhang; Jiabo Yin; Weibo Liu; Qian Cheng; Xiao Li; Dongyang Han; Liting Zhou; Huan Xu (Journal of Environmental Management, 2026)

Functional characterization of the CCL25/CCR9 axis in B cell differentiation and antibacterial defense in Nile tilapia - Yuhua Lin; Yiwen Chai; Jugan Han; Weiheng Shi; Along Gao; Jianmin Ye; Liting Wu (Aquaculture, 2026)

Sediment discharge regulates estuarine hypoxia: Coupled mechanisms of phosphorus limitation and organic carbon burial during the Yellow River WSRS - Longjiang Han; Honghua Shi; Liting Yin; Yong Liu; Wei Zheng; Weimin Wang; Zineng Yuan; Dewen Ding (Water Research, 2026)

Risk assessment and exposure patterns of hydroxypolycyclic aromatic hydrocarbons in elderly population: Insights from urinary metabolite levels and dietary habits - Yafei Gao; Biwen Wang; Liting Hua; Juanhua Li; Junqi Liu; Yang Peng; Lu Cheng; Hongkai Zhu; Hongwen Sun; Han Li; Hongzhi Zhao (Journal of Environmental Sciences, 2026)

Nitrogen Dominates Sedimentary Organic Carbon Distribution in a Tropical Marine Ranch - Xiaoran Shi; Liting Chen; Aiyao Yang; Yu Han; Xiaoju Pan; Zhaoyun Wang; Weijie Gong; Xiangen Wu (Journal of Marine Science and Engineering, 2026)
Marine ranching, as a pivotal strategy for enhancing the ocean’s carbon sequestration potential, offers significant potential to mitigate nearshore fishery depletion and restore marine ecosystems amid the global carbon neutrality agenda. However, the mechanistic pathways linking sediment total organic carbon (TOC) to various environmental factors in tropical marine ranches remain insufficiently quantified. This study selected the Wuzhizhou Island Marine Ranch in Hainan Province—a representative tropical marine ranch—as the research site. Field investigations and sampling were conducted during the dry (March 2024) and wet (September 2024) seasons to quantify TOC in surface sediments and associated environmental variables. A two-step analytical framework, integrating Principal Component Analysis (PCA) and Generalized Additive Models (GAM), was employed to elucidate the environmental drivers governing the spatiotemporal dynamics of TOC. The results show that the surface sediment TOC at Wuzhizhou Island Marine Ranch exhibits a distinct spatial gradient—Core Reef > Atoll > Control > Estuarine, and a pronounced seasonal pattern with elevated concentrations in the dry season relative to the wet season. The spatiotemporal differentiation of TOC is mainly driven by a gradient (explaining 52.1% of variation) that encompasses processes related to carbon accumulation from terrestrial inputs and primary production, as well as organic matter degradation promoted by nutrients and higher water temperatures. Sediment total nitrogen (TN) emerges as the primary environmental driver of TOC distribution, contributing up to 46.9% of the variance at an extremely significant level (p

Interactions of microbiota during solid-state cereal vinegar fermentation - Dantong Liu; Zhenhua Su; Qi Han; Liting Wang; Linna Tu; Yongjian Yu; Menglei Xia; Yanbing Shen; Yu Zheng; Min Wang (Trends in Food Science & Technology, 2026)

Predicting macrolide resistance in pediatric Mycoplasma pneumoniae pneumonia: A machine learning modeling study - Shuo Yang; Xinying Liu; Huizhe Wang; Yaowei Han; Dan Sun; Huanmin Li; Liting Ma; Haokai Wang; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Calenduloside E produced by Bifidobacterium animalis B960 increases glibenclamide efficacy and alleviates drug-induced adverse effects in a type 2 diabetes model - Siyuan Shen; Liting Lu; Haiyang Tu; Shuaiming Jiang; Zeng Zhang; Zhe Han; Jiachao Zhang (Science Bulletin, 2026)

Failure mode and bearing capacity of steel dual-angle (SDA) around real axis and imaginary axis under eccentric compressive load - Wanzhi Zhou; Yonghao Peng; Qin Wang; Liting Han; Fenghua Huang; Dachang Zhang (Ocean Engineering, 2026)

Promotion of waste sludge and corn straw co-composting by the new green conditioning agent of biomass power plant ash: Enhancement in organic matter bioconversion, nitrogen retention and functional bacterial metabolism - Lulu Qian; Ruidi Zhao; Qianyi Wang; Xiaona Wang; Meichao Zhao; Liting Zhai; Xiaoyu Han; Xin Zhao (Journal of Environmental Chemical Engineering, 2026)

Failure mechanism and bearing capacity of reinforced CHS X-joint under compressive load: Numerical simulation and theoretical analysis - Jie Zeng; Wanzhi Zhou; Yixin Xie; Liting Han; Dachang Zhang (Engineering Structures, 2026)

Amino acid-induced supramolecular assembly defective carbon nitride for efficient photocatalytic CO2 reduction - Rui Li; Liting Lai; Si Li; Shipeng Wan; Wenbei Jia; Yu Han; Ruixuan Chu; Qin Zhong; Zhaoxiang Zhong (Chemical Engineering Journal, 2025)

How Environment Affects Ontogenetic Differences in Leaf Functional Traits of Woody Plants - Ziyan Zhang; Kouki Hikosaka; Ülo Niinemets; Qingmin Han; Jeannine Cavender‐Bares; Liting Zheng; Dong He; Enrong Yan; Mengguang Han; Guangze Jin; Zhili Liu (Global Ecology and Biogeography, 2025)
Aim The consistency of patterns in ontogenetic differences in plant traits across the globe has not been thoroughly studied. Environmental conditions affect leaf functional traits, and these effects can differ between adult trees and saplings due to varying environmental conditions in their aerial and soil environments. Our integrative analysis aims to reveal the global universality of woody plants' ontogeny and explores influencing factors. Location Global. Time Period Studies published in 1989–2023. Major Taxa Studied Woody plants. Methods We performed a global meta‐analysis of woody plants with different plant functional types at 64 sites around the world, assessed the ontogenetic differences in nine key leaf traits and explored the environmental factors that affected the ontogenetic differences. Results We observed that (1) leaf traits differed significantly between adult trees and saplings, with environmental factors playing varying roles. Photosynthetic capacity per unit area ( A a ) and nitrogen content per unit dry mass ( N m ) were lower in saplings than in adults under low solar radiation, but this trend reversed with increased solar radiation. Differences in stomatal density (SD) and stable carbon isotope composition (δ 13 C) between adults and saplings were greatest under low solar radiation; (2) ontogenetic differences in leaf thickness (LT), leaf dry mass per area (LMA) and stomatal conductance ( g s ) were greater at lower mean annual temperature (MAT); (3) at high mean annual precipitation (MAP), adults had higher nitrogen content per unit area ( N a ), while saplings had higher N m than adults; (4) soil conditions were strongly correlated with ontogenetic differences in LT and SD, with soil pH as a key driver of variation in A a , LT, SD, N a and N m . Main Conclusions Our findings indicate that ontogeny strongly modifies leaf functional traits and that multiple environmental factors influence the magnitude of ontogenetic differences in leaf traits. This underscores the importance of considering ontogeny when predicting trait values across plant developmental stages, modelling vegetation composed of individuals of different ages and forecasting vegetation responses to environmental changes.

Abundant taxa enhanced stability of fungal communities according to reduced nitrogen fertilization - Heming Han; Bo Zhang; Hao Liu; Yue Li; Xu Weidong; Liting Zhang; Hui Cao; Feng Wang (Soil and Tillage Research, 2025)

Distribution and relationship of heavy metals, microbial communities and antibiotic resistance genes in the riparian soils of Daye Lake, China - Liting Yang; Jing Li; Bingyao Liu; Han Xu; Xuanzi Guo; Jing Wang; Yao Zhang (Environmental Geochemistry and Health, 2025)

Reapplication of glyphosate mitigate fitness costs for soil bacterial communities - Hao Liu; Cunzhi Zhang; Bo Zhang; Weidong Xu; Ruoling Zhang; Liting Zhang; Yue Li; Heming Han; Hui Cao (Journal of Environmental Management, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Identification and expression profiles of granzyme genes in immune response from Nile tilapia (Oreochromis niloticus) - Yiwen Chai; Yuhua Lin; Jugan Han; Weiheng Shi; Yiqing Wang; Along Gao; Liting Wu; Jianmin Ye (Aquaculture, 2025)

CXCL13/CXCR5 axis mediates IgM+ B cell migration through AKT and STAT3 signaling pathways in Nile tilapia (Oreochromis niloticus) - Yuhua Lin; Yiwen Chai; Along Gao; Jugan Han; Yanxi Guo; Yuqing Lin; Liting Wu; Jianmin Ye (Aquaculture, 2024)

Insight into the differential response of functional denitrifiers to novel formulated organic amendments in soybean agroecosystem - Ugochi Uzoamaka Egbeagu; Yue Zhang; Yuanhang Wang; Ayodeji Bello; Liting Deng; Yu Sun; Yue Han; Liyan Zhao; Shuai Shi; Huajing Liu; Xiuhong Xu (Rhizosphere, 2024)

Metabolic perturbations and bacterial communities dysbiosis associated with skin ulcer disease progression in Sepia pharaonis - Liting Xu; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Sheng Li; Weiwei Zhang; Qingxi Han (Aquaculture, 2024)

Frequency-specific functional difference between gyri and sulci in naturalistic paradigm fMRI - Liting Wang; Yang Yang; Xintao Hu; Shijie Zhao; Xi Jiang; Lei Guo; Junwei Han; Tianming Liu (Brain Structure and Function, 2024)

Comparative proteomic analysis of the protein profile in the cuttlefish Sepia pharaonis associated with skin ulceration syndrome - Haijuan Dai; Liting Xu; Maowang Jiang; Weiwei Zhang; Qingxi Han (Fish & Shellfish Immunology, 2024)

Bioaugmentation treatment of coal chemical reverse osmosis concentrate in biological contact oxidation system coupled with ozone pretreatment - Xushen Han; Liting Huang; Yan Jin; Jianguo Yu (Journal of Cleaner Production, 2023)

Benzo[a]pyrene-induced up-regulation of circ_0003552 via ALKBH5-mediated m6A modification promotes DNA damage in human bronchial epithelial cells - Shuwei Yao; Xintong Chen; Ningdong Hu; Nan Zhang; Miaoyun Qiu; Yangyang Jia; Han Zhang; Jihuan Liang; Zehao Chen; Liting Zheng; Jialu Zhu; Rulin Mao; et al. (Environmental Pollution, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

A new strategy for the enrichment of ammonia-oxidizing archaea in wastewater treatment systems: The positive role of quorum-sensing signaling molecules - Peihan Zheng; Qian Zhang; Jiaxing Zou; Qi Han; Jiarong Han; Qixin Wang; Liting Yao; Guangwei Yu; Yuhai Liang (Science of The Total Environment, 2023)

Succession of bacterial communities during a disease progress in cuttlefish Sepia pharaonis - Liting Xu; Yilong Ruan; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Weiwei Zhang; Qingxi Han (Aquaculture International, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Deciphering biochar compost co-application impact on microbial communities mediating carbon and nitrogen transformation across different stages of corn development - Ayodeji Bello; Wanying Liu; Nuo Chang; Kehinde Olajide Erinle; Liting Deng; Ugochi Uzoamaka Egbeagu; Busayo Joshua Babalola; Han Yue; Yu Sun; Zimin Wei; Xiuhong Xu (Environmental Research, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Building the Chordata Olfactory Receptor Database using more than 400,000 receptors annotated by Genome2OR - Wei Han; Yiran Wu; Liting Zeng; Suwen Zhao (Science China Life Sciences, 2022)

Effects of feed transition on digestive tract digestive enzyme, morphology and intestinal community in cuttlefish (Sepia pharaonis) - Maowang Jiang; Wencheng Xiao; Jingtao Ye; Liting Xu; Ruibing Peng; Qingxi Han; Zhenming Lü; Huilai Shi; Xiamin Jiang (Frontiers in Marine Science, 2022)
Sepia pharaonis is an excellent candidate for aquaculture in China. However, the low survival rate during early feed transition is a bottleneck restricting industrial development. Understanding the changes in digestive physiology and intestinal microflora during feed transition should enable us to meet their nutritional needs to improve production. In this study, we investigate the digestive enzyme of S. pharaonis and undertake histological observations of the digestive gland and intestine. The intestinal microflora 16S rRNA genes were also analyzed using high-throughput sequencing of the pre, mid, and post-feed transition stages (20, 40, and 60 days post-hatching (DPH), respectively). The digestive enzymes from the digestive gland (trypsin and chymotrypsin) rapidly decrease at 40 DPH when compared to their levels at 20 DPH, but mostly recovered by 60 DPH. The alkaline phosphatase and lipase increased sharply by 40 DPH, then peaked at 60 DPH. The intestinal digestive enzymes followed similar trends during feed transition, except for lipase activity, which decreased after 20 DPH and remained low, even at 60 DPH. Feed transition affects the morphogenesis of the digestive tract and feed transition stress leads to the impairment of the digestive gland and intestinal morphology, which reduces the digestive capacity, but almost totally recovers by 60 DPH. Moreover, the comparison of the intestinal microbial composition during feed transition revealed that the dominant phylum Bacteroidetes gradually increased to a peak at 40 DPH and then decreased until 60 DPH. The microbial composition changed with the most abundant genus Pseudomonas being replaced by Acinetobacter . The phylum and family level investigation suggested the microbiota in the rearing water had limited influence on the intestinal microbiota. The intestinal microbiota diversity increased during feed transition. This study improves our understanding of changes and adaptations in cuttlefish during feed transition.

Molecular cloning, characterization and expression analysis of CXCR3a and CXCR3b from Nile tilapia ( Oreochromis niloticus ) - Along Gao; Liting Wu; Lan Li; Biao Han; Jianmin Ye (Journal of Fish Biology, 2022)
The CXC chemokine receptors (CXCRs) are members of the seven transmembrane (7‐TM) G‐protein‐coupled receptor superfamily that involves innate and adaptive immune systems. In this study, CXCR3a and CXCR3b from Nile tilapia ( Oreochromis niloticus ) were cloned and identified, designated as OnCXCR3a and OnCXCR3b . The open reading frames of OnCXCR3a and OnCXCR3b were 1074 and 1080 bp, encoding the predicted proteins of 357 and 359 amino acids, respectively. Multiple alignment analysis of OnCXCR3a‐ and OnCXCR3b‐deduced protein sequences with the mammalian and bird sequences indicated the presence of typical structural features of chemokine receptors, including a 7‐TM domain and conserved motifs. Quantitative real‐time PCR analysis revealed that OnCXCR3a and OnCXCR3b were constitutively expressed in a wide range of tissues. When stimulated with Streptococcus agalactiae , Aeromonas hydrophila , polyinosinic:polycytidylic acid and lipopolysaccharide in vivo or in vitro on leukocytes, the mRNA levels of OnCXCR3a and OnCXCR3b were significantly upregulated. Overall, these results indicated that OnCXCR3s might be involved in host immune responses in Nile tilapia.

DNA methylation of JAK3/STAT5/PPARγ regulated the changes of lipid levels induced by di (2-ethylhexyl) phthalate and high-fat diet in adolescent rats - Qi Xu; Wen Qi; Yuezhu Zhang; Qi Wang; Shuang Ding; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2020)

Fungal community succession under influence of biochar in cow manure composting - Xin Jiang; Liting Deng; Qingxin Meng; Yu Sun; Yue Han; Xiaotong Wu; Siyuan Sheng; Haifeng Zhu; Bello Ayodeji; Ugochi Uzoamaka Egbeagu; Xiuhong Xu (Environmental Science and Pollution Research, 2020)

Correction to: Effects of di (2-ethylhexyl) phthalate and high-fat diet on lipid metabolism in rats by JAK2/STAT5 - Yuezhu Zhang; Liting Zhou; Zhaoming Zhang; Qi Xu; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Lin Ye (Environmental Science and Pollution Research, 2020)

Effects of di (2-ethylhexyl) phthalate and high-fat diet on lipid metabolism in rats by JAK2/STAT5 - Yuezhu Zhang; Liting Zhou; Zhaoming Zhang; Qi Xu; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Lin Ye (Environmental Science and Pollution Research, 2020)

Bis(propyl)-cognitin Prevents β-amyloid-induced Memory Deficits as Well as Synaptic Formation and Plasticity Impairments via the Activation of PI3-K Pathway - Liting Jiang; Meng Huang; Shujun Xu; Yu Wang; Pengyuan An; Chenxi Feng; Xiaowei Chen; Xiaofei Wei; Yifan Han; Qinwen Wang (Molecular Neurobiology, 2016)